Interaction of Mal de Río Cuarto virus (Fijivirus genus) proteins and identification of putative factors determining viroplasm formation and decay - Llauger, Gabriela; De Haro, Luis Alejandro; Alfonso, Victoria; Del Vas, Mariana (2017)
Mal de Río Cuarto virus (MRCV) is a member of the Fijivirus genus, within the Reoviridae family, that repli-cates and assembles in cytoplasmic inclusion bodies called viroplasms. In this study, we investigatedinteractions between ten MRCV proteins by yeast two-hybrid (Y2H) assays and identified interactionsof non-structural proteins P6/P6, P9-2/P9-2 and P6/P9-1. P9-1 and P6 are the major and minor compo-nents of the viroplasms respectively, whereas P9-2 is an N-glycosylated membrane protein of unknownfunction. Interactions involving P6 and P9-1 were confirmed by bimolecular fluorescence complementa-tion (BiFC) in rice protoplasts. We demonstrated that a region including a predicted coiled-coil domainwithin the C-terminal moiety of P6 was necessary for P6/P6 and P6/P9-1 interactions. In turn, a shortC-terminal arm was necessary for the previously reported P9-1 self-interaction. Transient expression ofthese proteins by agroinfiltration of Nicotiana benthamiana leaves showed very low accumulation levelsand further in silico analyses allowed us to identify conserved PEST degradation sequences [rich in pro-line (P), glutamic acid (E), serine (S), and threonine (T)] within P6 and P9-1. The removal of these PESTsequences resulted in a significant increase of the accumulation of both proteins.